Low electric field DNA separation and in‐channel amperometric detection by microchip capillary electrophoresis. Issue 2 (1st June 2014) - Ghanim, Motasem Hilmi; Najimudin, Nazalan; Ibrahim, Kamarulazizi; Abdullah, Mohd Zaid
Abstract : Miniaturisation of microchip capillary electrophoresis (MCE) is becoming an increasingly important research topic, particularly in areas related to micro total analysis systems or lab on a chip. One of the important features associated with the miniaturised MCE system is the portable power supply unit. In this work, a very low electric field MCE utilising an amperometric detection scheme was designed for use in DNA separation. The device was fabricated from a glass/polydimethylsiloxane hybrid engraved microchannel with platinum electrodes sputtered onto a glass substrate. Measurement was based on a three‐electrode arrangement, and separation was achieved using a very low electric field of 12 V/cm and sample volume of 1.5 µl. The device was tested using two commercial DNA markers of different base pair sizes. The results are in agreement with conventional electrophoresis, but with improved resolution. The sensitivity consistently higher than 100 nA, and the separation time approximately 45 min, making this microchip an ideal tool for DNA analysis.